2021
DOI: 10.3389/fphys.2021.672027
|View full text |Cite
|
Sign up to set email alerts
|

The Vagus Nerve and Spleen: Influence on White Adipose Mass and Histology of Obese and Non-obese Rats

Abstract: The vagus nerve (VN) and spleen represent a complex interface between neural and immunological functions, affecting both energy metabolism and white adipose tissue (WAT) content. Here, we evaluated whether vagal and splenic axis participates in WAT mass regulation in obese and non-obese male Wistar rats. High doses of monosodium glutamate (M; 4 g/Kg) were administered during the neonatal period to induce hypothalamic lesion and obesity (M-Obese rats). Non-obese or Control (CTL) rats received equimolar saline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Autonomic imbalance is an important element of adiposity in this obesity model (Miranda et al, 2016;Yoshida et al, 1985). It has been shown that vagal hyperactivity promotes hyperinsulinaemia and favours adipogenesis in MSG-obese rats (Kuchler et al, 2021;Miranda et al, 2016;Siqueira et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Autonomic imbalance is an important element of adiposity in this obesity model (Miranda et al, 2016;Yoshida et al, 1985). It has been shown that vagal hyperactivity promotes hyperinsulinaemia and favours adipogenesis in MSG-obese rats (Kuchler et al, 2021;Miranda et al, 2016;Siqueira et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Autonomic imbalance is an important element of adiposity in this obesity model (Miranda et al., 2016; Yoshida et al., 1985). It has been shown that vagal hyperactivity promotes hyperinsulinaemia and favours adipogenesis in MSG‐obese rats (Kuchler et al., 2021; Miranda et al., 2016; Siqueira et al., 2021). Moreover, reduced sympathetic activity leads to a lesser lipolytic effect on WAT and a reduction in thermogenic responsiveness of BAT in MSG‐obese rodents (Yoshida et al., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Weekly body weight and body length (nose-to-anus length, LNA) were recorded and were used to determine the lee index of obesity using the formula: [3√poids corporel (g)/LNA (cm) x 1000]. The lee index is considered as a good marker of adiposity [34,35].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…In summary, promoting WAT Browning is of great significance for the regulation and improvement of metabolic disorders in clinical obese patients, and it is also a hot topic in Western medicine treatment of obese patients in recent years. Studies have shown that WAT Browning is driven by norepinephrine released by sympathetic nerves [8][9]. Norepinephrine stimulates lipolysis and upregulates UCP1 through cyclic adenosine phosphate (cAMP).…”
Section: Wat and Bat Conversionmentioning
confidence: 99%